Five Transitions of Algorithmic Governmentality in the Composition of Medical Temporality; [Cinco Transiciones de la Gubernamentalidad Algorítmica en la Composición de la Temporalidad Médica] - Castillo-Sepulveda, J (Pontificia Universidad Catolica de Valparaiso, 2025)
Artificial Intelligence has permeated multiple social scenarios and medicine is no exception. It is part of the recent hopes articulated to address issues related to the temporality of their usual routines. In this paper we analyze five transformations that Artificial Intelligence integrates in the ordering of medical temporality, considering how this is articulated to modifications in the dynamics of power formulated by the notion of algorithmic governmentality. To this end, we rely on a study of the health system in Chile, which considers the development of a multi-sited ethnography based on ministerial scenarios and public and private clinical care. We have produced information through focused ethnographies, news analysis and in-depth interviews with experts and professionals, and configured results based on abductive analysis. The five transitions described consider the algorithmic, iterative, itinerant, interstitial and organismic character of the temporality constituted by scenarios in which Artificial Intelligence participates. We conclude by taking up the link between these transformations in the apprehension of algorithmic governmentality for the medical field. © 2025 Pontificia Universidad Catolica de Valparaiso. All rights reserved.